Multiple renewable input and output emergency portable power supply - Suresh Thanakodi,; Ahmad Mujahid Ahmad Zaidi,; Azizi Miskon,; Nazatul Shiema Moh Nazar,; Nik Zamiri Nik Hanapi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Currently portable power supply unit either powered by diesel generator or solar powered are only able to supply for alternating current (AC) or single direct current (DC) loads. In this work, multiple renewable input and output emergency portable power supply (E-PPS) prototype were developed and the functionality were explored. The developed prototype usage duration was determined by varying electrical loads. Verifications were carried out to demonstrate E-PPS functionality and usage during emergency with Malaysian Health-care Department, Malaysian Civil Defence Agency, and Malaysian Royal Signals Regiment. It was found that E-PPS managed to successfully supply simultaneous power for both alternating current (AC) and various direct current (DC) loads at an average of 88% efficiency.